Ultrasonic investigations of inclusion complexes of α-cyclodextrin with sodium alkyl sulfates. Kinetic and thermodynamic parameters - JUSZKIEWICZ, A.; BALCERZAK, A. (Archives of Acoustics, 1996)
Velocity and attenuation measurements of ultrasonic waves in aqueous solutions of α-cyclodextrin containing different sodium alkyl sulfates were made. The occurrence or an ultrasonic relaxation process, most probably connected with a deeper penetration of the alkyl chain into the cyclodextrin cavity and a more tight structure of the inclusion complexes of α-cyclodextrin with sodium decyl-, dodecyl- and tetradecyl sulfates, has been established. Thermodynamic and kinetic parameters related to this process have been calculated.